2015
DOI: 10.7763/ijssh.2015.v5.498
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Eat Traditional Food among Boys and Girls in Malaysia

Abstract: Abstract-Traditional foods serve as representation of culture and tradition of a country and are passed from one generation to another. The cuisines are prepared using fresh ingredients containing beneficial nutrients which protect human body from food-related diseases. Unfortunately, in this modern environment, adolescents nowadays seem to consume less traditional food compared to their ancestors due to various factors. This study investigates the differences in terms of intention to eat traditional food betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This study has enabled the conclusion that traditional food is important in giving meaning and identity in people's life and it is crucial to keep it that way It was found that there was no significant difference in terms of the results between the previous studies (Muhammad et al, 2015) as compared to this study where the PBC appeared to be the highest determinant in determining the intention to eat traditional food among students of UiTM Cawangan Terengganu Kampus Dungun. This is due to the way of life, for school children are shaped by their parents and are mostly influenced by family and friends as compared to university students, who live independently (Kimura et al, 2010) and no longer conform to their parents and family way of life (Savage et al, 2007).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This study has enabled the conclusion that traditional food is important in giving meaning and identity in people's life and it is crucial to keep it that way It was found that there was no significant difference in terms of the results between the previous studies (Muhammad et al, 2015) as compared to this study where the PBC appeared to be the highest determinant in determining the intention to eat traditional food among students of UiTM Cawangan Terengganu Kampus Dungun. This is due to the way of life, for school children are shaped by their parents and are mostly influenced by family and friends as compared to university students, who live independently (Kimura et al, 2010) and no longer conform to their parents and family way of life (Savage et al, 2007).…”
Section: Discussionmentioning
confidence: 46%
“…Most of the time, both parents are the main influencers that will shape and determine the eating behaviour of their children. This can be seen through the eating behaviour of school children as the children would not have many choices to eat something that they want as it will be determined by their parents (Muhammad et al, 2015). This is an example of social norms that is happening in our daily life and the intention of eating traditional food can be said to be controlled, namely, by the parents.…”
Section: Social Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Muhammad, Zahari, et al (2015) state the ideal time to transmit the knowledge of traditional food is during celebrations and religious festivals. In other hand, Muhammad, Karim, et al (2015) found that school activities such as cultural event and festive season may attract boys more than girls. Thus, it is important to introduce traditional food not just during festivals but also instill in the school activities to promote awareness of the traditional food.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2014), organic food (Boniface, 2012) and Halal food (Khalek and Ismail, 2015). Relevant studies, especially pertaining to the willingness to try new food among younger generations, are predominantly about soft drinks (Shahid et al, 2014), fast food (Delvarani, 2013) and Malay traditional food (Muhammad et al, 2015). Notwithstanding the abundance of literature on food consumption, the lack of Malaysian research on Dayak food consumption intention and behaviour demonstrates a huge gap in the literature.…”
Section: Hypotheses Developmentmentioning
confidence: 99%